2020
DOI: 10.1177/0033354920970947
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Health Record Reminders for Chlamydia Screening in an American Indian Population

Abstract: Objectives Indian Health Service (IHS) screening rates for Chlamydia trachomatis are lower than national rates of chlamydia screening in the Southwest. We describe and evaluate the effect of a public health intervention consisting of electronic health record (EHR) reminders to alert health care providers to screen for chlamydia at an IHS facility. We also conducted an awareness presentation among health care providers on chlamydia screening. Methods We conducted our intervention from November 1, 2013, through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The six IHS studies showed the capability of implementing CDS to promote change over large geographic areas with externally-available population-specific CDS and quality improvement methods [33,34,36,40,42,64]. Beginning in 2004, federally operated IHS facilities began implementing a single EHR, Resource and Patient Management System (RPMS), that was developed for IHS with end-user input and major contributions for shared core applications from the Department of Veterans Affairs legacy EHR, Veterans Health Information Systems and Technology Architecture (VistA) [71,72].…”
Section: Discussionmentioning
confidence: 99%
“…The six IHS studies showed the capability of implementing CDS to promote change over large geographic areas with externally-available population-specific CDS and quality improvement methods [33,34,36,40,42,64]. Beginning in 2004, federally operated IHS facilities began implementing a single EHR, Resource and Patient Management System (RPMS), that was developed for IHS with end-user input and major contributions for shared core applications from the Department of Veterans Affairs legacy EHR, Veterans Health Information Systems and Technology Architecture (VistA) [71,72].…”
Section: Discussionmentioning
confidence: 99%
“…Six references described an outbreak response for syphilis 4 and gonorrhoea. 2 STI testing and treatment within the Indian Health System are primarily provided in outpatient clinics and emergency departments 37,[73][74][75][76][77][78][79][80][81] and are delivered according to national guidelines. 73 Expedited partner therapy (EPT) is available in some clinical settings.…”
Section: Clinical Service Deliverymentioning
confidence: 99%
“…83,84 Clinical decision support in electronic health records is utilised at many facilities as testing bundles or screening reminders for bacterial STIs and HIV with a single order set to enhance screening. [76][77][78][79] In some situations, such as outbreaks or in review of local epidemiology, STI screening and clinical decision support can be expanded based on local policy and practice needs. 77,80,81 In comparison to non-Hispanic Whites, AI/AN men and women have been reported to more likely seek STI services.…”
Section: Clinical Service Deliverymentioning
confidence: 99%
“…3 Clinical decision support tools integrated into the electronic health record (EHR) have been used to increase screening for multiple conditions in primary care. 4,5,6 Alerts must be userfriendly and integrate smoothly into clinical workflows. 7,8,9 This quality improvement (QI) study describes implementation of an EHR alert to facilitate routine opt-out screening for HIV in an urban academic ED and reports the number of patients successfully linked to care.…”
Section: Introductionmentioning
confidence: 99%
“…3 Clinical decision support tools integrated into the electronic health record (EHR) have been used to increase screening for multiple conditions in primary care. 4,5,6 Alerts must be user-friendly and integrate smoothly into clinical workflows. 7,8,9…”
Section: Introductionmentioning
confidence: 99%